Antimicrobial activity of cephamycins and β-lactam/β-lactamase inhibitors against ESBL-producing Escherichia coli and Klebsiella pneumoniae under standard and high bacterial inocula - Yu Mi Wi; Ji Young Choi; Da Eun Lee; So Hyun Jun; Ki Tae Kwon; Kwan Soo Ko (Scientific Reports)
Abstract This study investigated the in vitro antimicrobial activity of cephamycins and novel β-lactam/β-lactamase inhibitor combinations, against extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae isolates. ESBL-producing blood isolates were obtained between January and May 2023. The antibiotic susceptibility of the isolates was determined by broth microdilution method using standard (105 CFU/mL) and high (107 CFU/mL) inoculum sizes. Two randomly selected ESBL-producing isolates were subjected to time-kill assays for cephamycin. More than 80% of the isolates exhibited susceptibility to cefoxitin, cefmetazole, flomoxef, ceftazidime/avibactam, cefepime/enmetazobactam and imipenem/relebactam. Ceftolozane/tazobactam demonstrated in vitro efficacy against 62.1% of the ESBL-producing isolates. At the higher inoculum size, cefoxitin, cefmetazole, flomoxef, ceftolozane/tazobactam, ceftazidime/avibactam, cefepime/enmetazobactam, and imipenem/relebactam demonstrated in vitro efficacy against 48.3%, 75.9%, 70.0%, 0%, 82.8%, 100%, 89.7% of the ESBL-producing isolates. The frequencies of the inoculum effect with cefoxitin (3.7%), cefmetazole (14.8%), flomoxef (88.9%), ceftolozane/tazobactam (96.0%), ceftazidime/avibactam (34.5%), cefepime/enmetazobactam (10.3%), and imipenem/relebactam (10.3%) were identified. With standard inoculum, cephamycins reduced bacterial growth within 2–24 h. However, high inoculum resulted in regrowth after 12 h of cephamycin exposure. Cephamycins demonstrated high in vitro activity against ESBL-producing isolates at standard inoculum sizes. However, the in vitro time-kill experiments revealed that the efficacy of cephamycins is not fully maintained at high inoculum sizes.